2018
DOI: 10.2147/ijn.s161423
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscaled and microscaled parallel topography promotes tenogenic differentiation of ASC and neotendon formation in vitro

Abstract: BackgroundTopography at different scales plays an important role in directing mesenchymal stem cell differentiation including adipose-derived stem cells (ASCs) and the differential effect remains to be investigated.PurposeThis study aimed to investigate the similarity and difference between micro- and nanoscaled aligned topography for inducing tenogenic differentiation of human ASCs (hASCs).MethodsParallel microgrooved PDMS membrane and a parallel aligned electrospun nanofibers of gelatin/poly-ε-caprolactone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…Across this work, our findings were consistent with previous literature on mechanical and surface structure regulation of macrophages and tendon cells, individually [19,21,22,40]. Our work represents a knowledge advance in identifying how these individual responses augment and in some cases differ when these biophysical cues are applied in co-culture systems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Across this work, our findings were consistent with previous literature on mechanical and surface structure regulation of macrophages and tendon cells, individually [19,21,22,40]. Our work represents a knowledge advance in identifying how these individual responses augment and in some cases differ when these biophysical cues are applied in co-culture systems.…”
Section: Discussionsupporting
confidence: 90%
“…How biomaterial substrate mechanics and biochemistry interact to guide cell behavior has emerged as an important research topic with broad implications to biomaterial design [15][16][17]. Specifically for tendon repair, an aligned micro-or nanofiber structure is now understood to be a highly instructive biophysical cue that can direct tendon https://doi.org/10.1016/j.biomaterials.2020.120034 Received 30 March 2019; Received in revised form 4 April 2020; Accepted 5 April 2020 specific lineage differentiation [18][19][20][21][22][23][24][25]. Our own work has shown that deviations from aligned biomaterial surface structures may play a potentially important role in predisposing inflammatory response of attached tendon fibroblasts [26].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the authors employed PCL electrospun fibers with three different types of alignment: random (REF), aligned (AEF), and mesh (MEF). In addition to the influence on cell morphology exerted by the way of alignment and likely due to topography-related contact cues directing cell behavior (as reported also by others [ 9 , 70 , 111 , 112 ]), they observed an impact on MSC secretory profile. Namely, the expression and release of anti-inflammatory and wound healing-promoting factors, including COX2, PGE2, iNOS, TSG6, and TGFβ, and of the proangiogenic factors VEGF, HGF, and bFGF, which were increased in 3D-cultured MSCs as compared to cells cultured in a monolayer and, in particular, were higher in cells on AEF and MEF, as compared to those on REF [ 110 ].…”
Section: Msc-seeded Scaffolds As a Source Of Soluble Factorssupporting
confidence: 70%
“…Differing properties of biomaterials, caused by different manufacturing processes, are well known to alter the function of cells [42][43][44][45]. In this study, three different NFC dressings varying in topography and amount of NFC were studied with multiple cell densities in order to identify the optimal culture conditions for hASCs.…”
Section: Discussionmentioning
confidence: 99%